The Role of Ai In UMKM: How Artificial Intelligence Helps UMKM Survive And Thrive In The Digital Era In Medan City - Muhammad Faishal Annas; Elfitra Desy Surya (Journal of Research in Social Science and Humanities, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, yet face major challenges in digital transformation, particularly in adopting emerging technologies. This study aims to analyze how artificial intelligence (AI) adoption contributes to digital transformation and competitive advantage among MSMEs in Medan City. A quantitative approach was employed, involving 154 MSME respondents. The key variables examined include Diffusion of Innovation, Technology-Organization-Environment (TOE), Digital Transformation, and Competitive Advantage using SEM-PLS. The results indicate that both Diffusion of Innovation and TOE significantly influence Digital Transformation and Competitive Advantage. Moreover, Digital Transformation significantly mediates the effects of both independent variables on competitive advantage. This study highlights the critical role of digital readiness, organizational support, and AI integration in fostering sustainable competitiveness among MSMEs in the digital era.